The Effect of Self-Management based Motion Graphic Video on Anxiety in Students of SMAN 1 Parongpong - Rahmawati, Mega Nur; Lindayani, Linlin; Roswendi, Achmad Setya (Jurnal Pendidikan Keperawatan Indonesia, 2025)
Introduction: Anxiety is one of the most prevalent psychological problems among adolescents, particularly high school students who are in a critical developmental phase toward adulthood. If not properly managed, anxiety can negatively affect psychological well-being, academic performance, and social functioning. Poor self-management skills contribute to heightened anxiety levels, highlighting the need for effective, engaging, and easily accessible educational interventions. Motion graphics, as an interactive visual medium, have demonstrated potential in enhancing engagement and improving the effectiveness of psychoeducational interventions among adolescents. Objective: This study aimed to examine the effect of self-management–based motion graphic videos on anxiety levels among high school students and to evaluate the role of demographic factors in intervention outcomes. Methods: A quasi-experimental quantitative design was employed. From a population of 274 students identified with moderate anxiety levels, 128 students were selected using proportional random sampling and assigned to an intervention group (n = 64) or a control group (n = 64). The intervention group received a motion graphic–based self-management video, while the control group received conventional health education. Anxiety levels were measured using the State-Trait Anxiety Inventory (STAI). Data were analyzed using paired t-tests and ANCOVA. Results: The intervention group demonstrated a significant reduction in anxiety scores from pre-test (Mean ± SD = 51.7 ± 3.22) to post-test (Mean ± SD = 47.2 ± 3.54; p 0.005). ANCOVA results showed that age had a significant effect on post-test anxiety levels (p 0.05), whereas gender, parental education, and parental occupation did not show significant effects. Conclusion: Motion graphic–based self-management interventions are effective in reducing anxiety among adolescents. These findings support the integration of visually engaging, theory-based digital media into school-based mental health promotion and counseling programs.